Upaya Pemerintah Daerah dalam Mewujudkan Prinsip Tata Kelola Perusahaan Daerah yang Baik - Owa da Santo, Maria Fransiska; Wohon, Ernestha Uba; Lawalu, Emiliana Martuti (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The role of government investment through regional state-owned companies is an effort to strengthen regional revenue originating from separated regional assets. The purpose of establishing a regional limited liability company is as one of the drivers of regional economic growth and development. The purpose of this paper is to explain the role of local governments in realizing the management of regional companies based on the principles of good corporate governance. The research method used is normative legal research method. The regional government in its position as the majority shareholder has the authority to manage, regulate and intervene in the management of regional state-owned companies. As the majority shareholder, the local government has authority that is not delegated to the board of directors and commissioners. Likewise with the application of the principles of good corporate governance. The role of local government is to supervise, monitor and evaluate the implementation of the principles of good corporate governance developed within the company, especially for directors, commissioners and employees.